Physical and chemical characterization of dovyalis fruits - Lucena Cavalcante, Ítalo Herbert [UNESP]; Geraldo Martins, Antonio Baldo [UNESP] (Taylor & Francis, 2006)
The objective of this work was to establish physical and chemical characterizations of dovyalis hybrid fruits (Dovyalis abyssinica and D. hebecarpa). Samples of 25 fruits were characterized by evaluation of length and width, weight, percentage and number of seeds per fruit, peel percentage, pulp percentage, total soluble solids (TSS), titratable acidity (TA), vitamin C and TSS/TA ratio. Dovyalis fruit has good physical quality for market with an average of 75% pulp. Vitamin C content averaged 120.3 mg/100 g of fresh fruit, characterizing dovyalis as a good source of vitamin C. © 2005 by The Haworth Press, Inc. All rights reserved.
Keywords: Dovyalis hebecarpa; Dovyalis hybrid; Exotic plant Dovyalis abyssinica; Fruit quality; food market; fruit; nutritive value; Dovyalis; Dovyalis abyssinica